Caspase-10 inhibits ATP-citrate lyase-mediated metabolic and epigenetic reprogramming to suppress tumorigenesis - Rajni Kumari (Nature Portfolio, 2019)
Caspases are most closely associated with cell death, but many have other cellular functions. Here, Das et al. find that upon metabolic stress, caspase-10 cleaves ACLY to regulate metabolic homeostasis and epigenetic reprogramming by altering Acetyl-CoA levels.